Investigation of frequency characteristics of biological tissues impedance - Semenets, V.V.; Leonidov, V.I. (Radiotekhnika, 2020)
The problem of identifying informative signs of biological tissues viability using the impedance measurement method is formulated. At present there is no instrumental base that makes it possible in an operational setting to diagnose the ability of biological tissue to heal itself after injury and damage as a result of thermal exposure, gunshot wound or prolonged compression. It is shown in this article that development of methods and tools for instrumental diagnostics in medical diagnostic practice is an important modern challenge. The results of experimental measurements of impedance characteristics in the frequency range of 20 Hz – 2.0 MHz are presented. The frequency dependences of the modulus of voltage on biological tissues of plant origin are analyzed in its intact state, as well as after exposure of biological tissue samples in a freezer at time intervals from 15 minutes to 2 hours. A comparative analysis of the obtained frequency dependences is carried out. A significant difference between the frequency dependences of the voltage modulus on biological tissues and the frequency dependence of the voltage modulus on an isotonic solution is shown. The concept is introduced that the degree of difference between the frequency distribution of the biological tissue impedance module from the impedance module of an isotonic solution can serve as a criterion for assessing the degree of damage to biological tissue. A conclusion is made about the advisability of developing the impedance measurement method as a method for diagnosing the viability of biological tissue; it is shown that the most promising approach to the development of impedance measurement methods is the analysis of transient processes when biological tissue is disturbed by small electric current pulses.